PERAN KEPALA DESA SEBAGAI MOTIVATOR UNTUK MENINGKATKAN KESADARAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI DESA LUKBAYUR KECAMATAN TANTA KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
Efforts made by the Village Head to be able to invite taxpayers and the community in providing counseling, improving services and in awarding can increase public awareness to pay taxes. The aims of this study were: (1) to find out the factors that influence public awareness in Lukbayur Village in paying land and building tax, (2) to find out the efforts to increase public awareness in paying land and building tax, (3) to find out the obstacles that faced by the Village government to increase public awareness in Lukbayur Village in paying Land and Building Tax. The technique used in conducting research or data collection is by using a questionnaire, observation and documentation. In this study, for the purposes of data analysis, the authors did not use statistical analysis techniques in the sense that they were not related to scores and scales. The role of the Village Head as a Motivator to Increase the community in paying Land and Building Tax (PBB) has played a role, it's just that the realization has not been achieved and there is still a lack of public awareness of taxpayers. The level of awareness/compliance of taxpayers can be influenced by various factors, including lack of knowledge of taxation including sanctions in the field of taxation, lack of information regarding the role and function of taxes for state development, and income levels of taxpayers that are disproportionate to the amount of tax to be paid by taxpayers. Keywords: Role, Public Awareness, Tax.